(untitled) (American Journal of Islam and Society, 2015)
Zareena Grewal’s book traces the hopes, debates, accomplishments, and disappointments of American Muslim students who travel to the Middle East in pursuit of Islamic knowledge. As Grewal discovers through her interviews with over 100 students and teachers, the impetus behind many of their journeys is a desire to find a solution to the “crisis” of Islamic authority in the United States. But once they spend some time immersed in a predominantly Muslim society, many discover that this crisis extends to the Muslim world as well. More recently, some American Muslim scholars have shifted their attention away from the Middle East and toward an “indigenization” of American Islam, which, the author points out, also faces many challenges. In chapter 1 Grewal explains that her project is focused on student-travelers who view the Islamic East as an “Archive of Tradition” (p. 36) that they hope will provide a more authentic and authoritative form of Islamic knowledge than what they could learn in the United States. Her fieldwork took her to Amman, Damascus, and Cairo during the early 2000s, where she interviewed students of such figures as Shaykh Nuh Ha Mim Keller, Qubaysiya Ansa Tamara Gray, and Shaykh Ali Goma‘a, among others. The students she met came from diverse ethnic, geographic, and socio-economic backgrounds. Grewal does a good job of highlighting how these factors shaped their journeys ...